Mitasaqan Ghaliza's Concept as a Solution to the Feminist Perspective on the Concept of Marriage: Konsep Mitasaqan Ghaliza Sebagai Solusi Cara Pandang Feminis Tentang Konsep Pernikahan - Shalahuddin, Henri; Hidayat, Muhammad Sofian; Nugroho, Allam Setiawan; Tsaqib, M Ammar; Jamil, Ahmad (Center of Islamic and Occidental Studies, 2023)
This article focuses on the conception of marriage in Islam called mītsāqan ghalīzhan. In the context of this research, the concept of mītsāqan ghalīzhan is placed as a response to the problem of feminism's perspective that considers marriage and family to only bring misery and oppression to women. Using library research and content analysis methods, this study found that the concept of mīthsāqan ghalīzhan in Islamic marriage indicates a strong and holy covenant, accompanied by the values of devotion, harmony, and mutual understanding between husband and wife. This concept emphasizes loyalty, justice, and cohesion in the bond of marriage. Meanwhile, feminist views on marriage tend to focus on gender equality, rejection of patriarchal structures, and emphasis on women's rights.